Alienação fiduciária de bens imóveis no cenário jurídico e econômico do país - Lima, Ylka Iris Beltrão (2021)
The present work presents fiduciary alienation property aspects regulated by Law No. 9,514 / 97, addressing in this study its characteristics, nature, the legislative objective of its creation and the changes the Law has been undergoing since its promulgation until the current days, where we experienced a great economic and social crisis scenario due to the pandemic caused by Covid-19. The extrajudicial procedures constitutionality will also be analyzed, especially regarding to apply judicial principles possibility in the extrajudicial sphere. Brazil is a country which experiences economic crises real cycles, causing direct influence on the Law, introducing excessive changes in the legislation which suppress constitutionally guaranteed rights focusing to provide greater agility and security to grant credit through fiduciary alienation. However, the global proportion emergence crisis caused by Covid-19 pandemic, brought a more humanized look at economic order questions, particularly at Fiduciary Alienation Law, which had its provisions more relaxed by financial institutions for debts collection in this pandemic moment, which could be introduced into the referred legislation definitively without impacting on the reduction in credit or the delay in receiving it.